Norepinephrine enhances song responsiveness and encoding in the auditory forebrain of male zebra finches - Lee, Vanessa (J Neurophysiol, 2018)
Norepinephrine (NE) can dynamically modulate excitability and functional connectivity of neural circuits in response to changes in external and internal states. Regulation by NE has been demonstrated extensively in mammalian sensory cortices, but whether NE-dependent modulation in sensory cortex alters response properties in downstream sensorimotor regions is less clear. Here we examine this question in male zebra finches, a songbird species with complex vocalizations and a well-defined neural network for auditory processing of those vocalizations. We test the hypothesis that NE modulates auditory processing and encoding, using paired extracellular electrophysiology recordings and pattern classifier analyses. We report that a NE infusion into the auditory cortical region NCM (caudomedial nidopallium; analogous to mammalian secondary auditory cortex) enhances the auditory responses, burst firing, and coding properties of single NCM neurons. Furthermore, we report that NE-dependent changes in NCM coding properties, but not auditory response strength, are transmitted downstream to the sensorimotor nucleus HVC. Finally, NE modulation in the NCM of males is qualitatively similar to that observed in females: in both sexes, NE increases auditory response strengths. However, we observed a sex difference in the mechanism of enhancement: whereas NE increases response strength in females by decreasing baseline firing rates, NE increases response strength in males by increasing auditory-evoked activity. Therefore, NE signaling exhibits a compensatory sex difference to achieve a similar, state-dependent enhancement in signal-to-noise ratio and coding accuracy in males and females. In summary, our results provide further evidence for adrenergic regulation of sensory processing and modulation of auditory/sensorimotor functional connectivity. NEW & NOTEWORTHY This study documents that the catecholamine norepinephrine (also known as noradrenaline) acts in the auditory cortex to shape local processing of complex sound stimuli. Moreover, it also enhances the coding accuracy of neurons in the auditory cortex as well as in the downstream sensorimotor cortex. Finally, this study shows that while the sensory-enhancing effects of norepinephrine are similar in males and females, there are sex differences in the mode of action.